“DEVELOPING STUDENTS’ CREATIVITY AND CRITICAL THINKING THROUGH VISUAL ARTS EDUCATION IN SCHOOLS AND UNIVERSITIES” - Aslonova Shaxnoza Islom qizi (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
Abstract: This article examines the importance of visual arts education in enhancing students’ creativity and critical thinking in school and higher education. It emphasizes that early exposure to visual arts develops foundational skills, cognitive abilities, and imaginative thinking, while university education builds upon these foundations through advanced projects, interdisciplinary learning, and professional artistic practice. The study highlights the need for integrated visual arts curricula to foster holistic development and prepare students for creative careers.